Does a polyurethane film improve the burn healing properties of an ionic silver hydro-fiber dressing in the treatment of minor partial-thickness burns? A retrospective review of medical records comparing healing time, patient satisfaction and medical costs in two different treatment modalities - Sandra Johansson Vaage; Christina Brudvik; Hallvard Vindenes; Torbjørn Hiis Bergh; Knut Steen; Soosaipillai Bernardshaw (Elsevier, 2021)
Background: In the management of partial-thickness burns, insufficient data exist to recommend a specific dressing type. Silver dressings are often used, but different modalities have not been addressed. Methods: We performed a retrospective review of all medical records of burns treated at Bergen Minor Injury Department for 1 year. We compared the outcome from a moist treatment protocol, using an ionic silver hydro-fiber dressing (Aquacel® Ag) with an occlusive covering with a polyurethane film dressing (Tegaderm®), with an adherent treatment protocol using the same ionic silver hydro-fiber dressing without an occlusive covering on minor partial-thickness burns. Results: We included 213 patients attending Bergen Minor Injury Department (MID) with a minor partial-thickness burn during a one-year period (2018-2019). One hundred and nineteen burns were treated with an ionic silver hydro-fiber dressing and a polyurethane film dressing (Moist dressing group) and 94 wounds were treated with an ionic silver hydro-fiber dressing and dry gauze (Adherent dressing group). Most of the wounds involved less than 2% of total body surface area (TBSA) and were caused by scalds from hot liquids or contact burns from hot surfaces. The patients in the two treatment modalities had similar characteristics in respect to size, localisation, and cause of injury. Mean age was 25 years and genders were equally affected. The moist dressing group had less follow-up controls (0.45, 95% CI = 0.21 - 0.69, p < 0.05), less treatment time (2.27 days, CI 1.06-3.48, p < 0.005) and a higher rate of complete healing at final follow up (65.5% versus 41.5%, p < 0.005). Conclusion: Treatment with an ionic silver hydro-fiber dressing and a polyurethane film showed faster healing time, higher healing rate at final follow-up and less need for follow-ups. In minor burns, the moist treatment modality should be preferred to the traditional ionic silver hydro-fiber dressing that adheres to the wound.